Mucosal-Associated Invariant T (MAIT) cells are highly activated in duodenal tissue of humans with Vibrio cholerae O1 infection: A preliminary report. - Taufiqur R Bhuiyan; M Arifur Rahman; Shubhanshi Trivedi; Taliman Afroz; Hasan Al Banna; Mohammad Rubel Hoq; Ioana Pop; Owen Jensen; Rasheduzzaman Rashu; Muhammad Ikhtear Uddin; Motaher Hossain; Ashraful I Khan; et al. (Public Library of Science (PLoS), 2022)
Mucosal-associated invariant T (MAIT) cells are unconventional T lymphocytes with a semi-conserved TCRα, activated by the presentation of vitamin B metabolites by the MHC-I related protein, MR1, and with diverse innate and adaptive effector functions. The role of MAIT cells in acute intestinal infections, especially at the mucosal level, is not well known. Here, we analyzed the presence and phenotype of MAIT cells in duodenal biopsies and paired peripheral blood samples, in patients during and after culture-confirmed Vibrio cholerae O1 infection. Immunohistochemical staining of duodenal biopsies from cholera patients (n = 5, median age 32 years, range 26-44, 1 female) identified MAIT cells in the lamina propria of the crypts, but not the villi. By flow cytometry (n = 10, median age 31 years, range 23-36, 1 female), we showed that duodenal MAIT cells are more activated than peripheral MAIT cells (p < 0.01 across time points), although there were no significant differences between duodenal MAIT cells at day 2 and day 30. We found fecal markers of intestinal permeability and inflammation to be correlated with the loss of duodenal (but not peripheral) MAIT cells, and single-cell sequencing revealed differing T cell receptor usage between the duodenal and peripheral blood MAIT cells. In this preliminary report limited by a small sample size, we show that MAIT cells are present in the lamina propria of the duodenum during V. cholerae infection, and more activated than those in the blood. Future work into the trafficking and tissue-resident function of MAIT cells is warranted.